Answer:
6x² + 4x + 10
Step-by-step explanation:
(2x - 2)(3x + 5)
2x(3x + 5) - 2(3x + 5)
6x² + 10x - 6x + 10
6x² + 4x + 10 ans.
hope this helps you !
Answer:
C
Step-by-step explanation:
Answer:
6
Step-by-step explanation:
6s^2=s^3
divide by s^2 on both sides to get 6=s. There is your answer
Answer:
63.8
Step-by-step explanation:
to the tenth
Answer:
No answer as written. 16 if we add an equals sign.
Step-by-step explanation:
As written, there is no "=" sign in either expression. That means they are only expressions, not equations. x can be anything. 10, 12345, 0.00000343345567788, etc. There is nothing that restricts the value of x.
If we set the two expressions equal to each other, we can calculate a value of x:
(2x + 30) = (5x - 18)
3x = 48
x = 16